Pengaruh Penggunaan Media E-Learning Terhadap Kedisiplinan Siswa dalam Mata Pelajaran PABP Kelas VII di SMP Negeri 1 Ciwidey - Yusniar Puji Astuti (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
The objectives of this study are 1) To determine the use of E-learning media in class VII in PABP (Religious Education and Character Education) subjects at SMPN 1 Ciwidey. 2) To determine the discipline of class VII students in PABP subjects at SMPN 1 Ciwidey. 3) To determine the effect of using E-learning media on the discipline of class VII students in PABP subjects at SMPN 1 Ciwidey. The approach used in this study uses a quantitative approach. The method used in this research is descriptive method. The results in this study are, 1) the results of descriptive statistical testing of E-learning media get an average result of 45.62% with the most answers being